Knowledge about health service waste among health professionals in a municipality in central Tocantins state, Brazil (Research, Society and Development, 2021)
The objective of this work was to evaluate the knowledge about the management of health service waste among the professionals of the Basic Health Units of a municipality in the central region of the State of Tocantins, Brazil. It is a descriptive, exploratory study, with a quali-quantitative approach. The interviews were carried out with 89 health workers, being constituted a sample of 26 (29%) nurses, odontologists and doctors, and 63 (71%), professionals with high school education (community health agents, nursing technicians and oral health technicians). Among the workers with higher education 25 (96.1%) interviewed correctly conceptualized the RSS, thus demonstrating knowledge on the subject, however, among the workers with secondary education 48 (76.1%) gave an assertive response, drawing attention in this group the fact that 15 (23.8%) did not answer the question correctly. Waste from health services is still understood as hospital waste by most questionnaires and the perforating ones are the most mentioned.